Reactive Attachment Disorder and Its Relationship to Psychopathology: A Systematic Review - Florencia Talmón-Knuser; Francisco González-Sala; Laura Lacomba-Trejo; Paula Samper-García (Children, 2023)
This study aimed to determine, through a systematic review, the relationship between Reactive Attachment Disorder (RAD) and the presence of psychopathology in children and adolescents, and to determine the existence of differences in terms of internalising and externalising psychological problems between the RAD group and groups with other disorders or with typical development. Following the PRISMA methodology, a search was carried out in the Web of Science, PubMed and Scopus databases. The search yielded 770 results, of which only 25 met the inclusion criteria. The results indicate a relationship between the presence of RAD and/or disinhibited social engagement disorder (DSED), with the presence of internalising and externalising problems. These difficulties are more present in children with RAD compared to children without personal difficulties, or children with DSED, children with autism, children with intellectual disabilities or children with hyperactivity. It can be concluded that the presence of RAD has negative consequences on the mental health of children and adolescents, with these being greater in the inhibited group than in the disinhibited group, and with respect to children with autism or hyperactivity.